The transformation of the Turkish defence industry from the time of the Ottoman Empire to the Republic of Turkey, 1834-1950 - Kurt, Enes; Sehitoglu, Yasin (UNIV BARCELONA, DEPT HISTORIA, INST ECONOMIQUES, 2022)
This study examines the transformation of the Turkish defence industry between the years 1834 and 1950, defining periods to reveal the structure and conditions of the industry over that time. We identify the first period, which took place from 1834 to 1923, as one of Moderniza-tion efforts and import dependency; in this period, modernization efforts began and state in-itiatives introduced the steam engine to the Turkish defence industry. Activities undertaken during this period met with limited success, and towards the end of the century, the defence industry became completely dependent on imports. We identify the second period, which took place between the years 1923 and 1950, as one of Domestic production efforts; in this peri-od, especially in Ataturk's time (1923-1938), Turkey sought to establish local industry and an industrialist class with close ties to the state. That industrial policy came to an end following British military aid, World War II, and Turkey's entry to NATO.
Keywords: KEywoRDS; Turkish defence industry; Ottoman Empire; Turkish Republic; transforma-tion; Business & Economics; History; Social Sciences - Other Topics